Standardization of Polyherbal Extract for Type-2 Diabetes - Mittal; V. Juyal; A. Singh (Journal of Pharmacy and Nutrition Sciences, 2015)
Aims: This study was aimed to standardize the polyherbal extract containing Annona squamosa, Phyllanthus emblica, Berberis aristata and Curcuma longa for the management of type-2 diabetes. The standardization of polyherbal formulation is indispensable in order to achieve the quality, purity, safety and efficacy of drugs. Study Design: Physico-chemical investigations, Physical characteristics, Qualitative phytochemical analyses, fluorescence analysis and HPLC analysis. Materials and Methods: The Standardization of polyherbal extract was based on systematic organoleptic evaluation, physico-chemical investigation, physical characteristics, heavy metal analysis, fluorescence analysis, phytochemical screening, total alkaloid content, determination of viscosity, surface tension, density and HPLC analysis were carried out by official method. Results: Organoleptic evaluation resulted that it was yellowish green in colour with characteristic odour, bitter, pungent taste and fine texture. All the applied Physico-chemical parameters like total ash, acid insoluble, water soluble ash, extractive values, observed pH, moisture content, crude fibre, foaming index were found to be within limit. The limits obtained from physical and other parameters could be used as reference in quality control. The phytochemical analysis indicated the presence of alkaloids, carbohydrates, flavonoids, volatile oils, tannins, saponins, phytosterols and mucilage. Absence of detectable levels of heavy metal confirmed that extract was non-toxic in nature. HPLC studies confirm the presence of marker compounds in each extract. Conclusion: On the basis of observations and experimental results, the study can be used as reference standard for the further quality control research as it significantly ensures the use of genuine and uniform material and well-designed methodologies for standardization and development of poly herbal extract.